GREEN ENTREPRENEURSHIP EDUCATION: A SYSTEMATIC REVIEW OF TRENDS, INFLUENCING FACTORS, AND STRATEGIC IMPLEMENTATIONS IN HIGHER EDUCATION - Eka Imbia Agus Diartika; M. Ilham Nurhakim (Sampoerna University, 2026)
This study systematically reviews the development of Green Entrepreneurship Education (GEE) in higher education by examining research trends, influencing factors, and implementation strategies that foster Green Entrepreneurial Intention (GEI) and Green Entrepreneurial Behavior (GEB). Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 20 Scopus-indexed articles published between 2015 and 2025 were selected and analyzed thematically. The findings indicate a notable increase in GEE-related publications since 2023, with entrepreneurship education, green entrepreneurial intention, green entrepreneurship, university students, and green entrepreneurial behavior emerging as dominant themes. This review contributes an integrated synthesis framework linking GEE determinants, implementation strategies, and the transition from intention to behavior. The results show that GEE implementation is influenced by curriculum design, institutional support, ecosystem collaboration, individual characteristics, social values, sustainability literacy, and policy contexts. Effective strategies include sustainability-oriented curricula, experiential learning, competency development, psychological empowerment, collaborative approaches, and external policy support. The review also identifies a major research gap: most studies emphasize entrepreneurial intention rather than actual behavior. Future studies should employ longitudinal and cross-contextual approaches to better explain and strengthen the intention–behavior transition in green entrepreneurship.